Pediatric Angioedema without Wheals: How to Guide the Diagnosis - Lucia Liotti; Luca Pecoraro; Carla Mastrorilli; Riccardo Castagnoli; Francesca Saretta; Francesca Mori; Stefania Arasi; Simona Barni; Mattia Giovannini; Lucia Caminiti; Michele Miraglia Del Giudice; Elio Novembre (Life, 2023)
Angioedema (AE) is a vascular reaction of subcutaneous and submucosal tissues that identifies various clinical pictures and often is associated with wheals. AE without wheals (AEwW) is infrequent. The ability to distinguish between AEwW mediated by mast cells and bradykinin-mediated or leukotriene-mediated pathways is often crucial for a correct diagnostic–therapeutic and follow-up approach. AEwW can be hereditary or acquired. Factors typically correlated with hereditary angioedema (HAE) are a recurrence of episodes, familiarity, association with abdominal pain, onset after trauma or invasive procedures, refractoriness to antiallergic therapy, and lack of pruritus. The acquired forms of AE can present a definite cause based on the anamnesis and diagnostic tests. Still, they can also have an undetermined cause (idiopathic AE), distinguished according to the response to antihistamine in histamine-mediated and non-histamine-mediated forms. Usually, in childhood, AE responds to antihistamines. If AEwW is not responsive to commonly used treatments, it is necessary to consider alternative diagnoses, even for pediatric patients. In general, a correct diagnostic classification allows, in most cases, optimal management of the patient with the prescription of appropriate therapy and the planning of an adequate follow-up.